Rehabilitation therapies for older clients of the Ontario home care system: Regional variation and client-level predictors of service provision - Armstrong, Joshua J.; Zhu, Mu; Hirdes, John P.; Stolee, Paul (Disability and Rehabilitation, 2015)
Purpose: To examine regional variation in service provision and identify the client characteristics associated with occupational therapy (OT) and physiotherapy (PT) services for older adults in the Ontario Home Care System. Methods: Secondary analyses of a provincial database containing comprehensive assessments (RAI-HC) linked with service utilization data from every older long-stay home care client in the system between 2005 and 2010 (n = 299 262). Hierarchical logistic regression models were used to model the dependent variables of OT and PT service use within 90 d of the initial assessment. Results: Regional differences accounted for 9% of the variation in PT service provision and 20% of OT service provision. After controlling for the differences across regions, the most powerful predictors of service provision were identified for both OT and PT. The most highly associated client characteristics related to PT service provision were hip fracture, impairments in activities of daily living/instrumental activities of daily living, cerebrovascular accidents, and cognitive impairment. For OT, hazards in the home environment was the most powerful predictor of future service provision. Conclusions: Where a client lived was an important determinant of service provision in Ontario, raising the possibility of inequities in access to rehabilitation services. Health care planners and policy makers should review current practices and make adjustments to meet the increasing and changing needs for rehabilitation therapies of the aging population.

Le vieillissement des francophones de l’Ontario. Livre blanc - Assemblée de la francophonie de l’Ontario (2019)

Prevalence and patterns of multimorbidity among linguistic groups of patients receiving home care in Ontario: a retrospective cohort study. - Batista, Ricardo; Reaume, Michael; Roberts, Rihannon; Seale, Emily; Rhodes, Emily; Sucha, Ewa; Pugliese, Michael; Kendall, Claire E.; Bjerre, Lise M.; Bouchard, Louise; Prud'homme, Denis; Manuel, Douglas G.; et al. (BMC Geriatr., 2023)
Background Prior studies have demonstrated the negative impact of language barriers on access, quality, and safety of healthcare, which can lead to health disparities in linguistic minorities. As the population ages, those with multiple chronic diseases will require increasing levels of home care and long-term services. This study described the levels of multimorbidity among recipients of home care in Ontario, Canada by linguistic group. Methods Population-based retrospective cohort of 510,685 adults receiving home care between April 1, 2010, to March 31, 2018, in Ontario, Canada. We estimated and compared prevalence and characteristics of multimorbidity (2 or more chronic diseases) across linguistic groups (Francophones, Anglophones, Allophones). The most common combinations and clustering of chronic diseases were examined. Logistic regression models were used to explore the main predictors of ‘severe’ multimorbidity (defined as the presence of five or more chronic diseases). Results The proportion of home care recipients with multimorbidity and severe multimorbidity was 92% and 44%, respectively. The prevalence of multimorbidity was slightly higher among Allophones (93.6%) than among Anglophones (91.8%) and Francophones (92.4%). However, Francophones had higher rates of cardiovascular and respiratory disease (64.9%) when compared to Anglophones (60.2%) and Allophones (61.5%), while Anglophones had higher rates of cancer (34.2%) when compared to Francophones (25.2%) and Allophones (24.3%). Relative to Anglophones, Allophones were more likely to have severe multimorbidity (adjusted OR = 1.04, [95% CI: 1.02–1.06]). Conclusions The prevalence of multimorbidity among Ontarians receiving home care services is high; especially for whose primary language is a language other than English or French (i.e., Allophones). Understanding differences in the prevalence and characteristics of multimorbidity across linguistic groups will help tailor healthcare services to the unique needs of patients living in minority linguistic situations.

La santé des personnes âgées francophones vivant en situation minoritaire au Canada : enjeux et besoins - Bouchard, Louise; Desmeules, Martin (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé L’objectif de ce chapitre est de présenter le profil sociodémographique et sanitaire de la population aînée francophone (65 ans et plus) vivant en situation linguistique minoritaire afin d’en ressortir les enjeux et les besoins qui la caractérisent. Nous aborderons dans un premier temps le fait minoritaire et son effet potentiel sur le vieillissement de la population et la position sociale des personnes âgées, leur santé et leur accès aux services. Une seconde section établira, à partir des données de l’Enquête sur la santé dans les collectivités canadiennes (ESCC, cycles combinés, 2003-2012), le portrait sociosanitaire des aînés en fonction de trois grandes régions canadiennes (les provinces de l’Atlantique, l’Ontario et les provinces de l’Ouest). Enfin, nous discuterons ici de deux enjeux qui nous apparaissent fondamentaux au regard de cette population minoritaire, soit celui de la littératie en santé, c’est-à-dire la capacité de communiquer et de naviguer adéquatement dans le système de santé, et celui de l’offre active de services, une mesure d’équité et de qualité des soins. Mots-clés : aînés francophones, minorités linguistiques, portrait sociosanitaire, Canada, Enquête sur la santé dans les collectivités canadiennes (ESCC).
Chapitre: 5

The health of Francophone seniors living in minority communities in Canada: Issues and needs - Bouchard, Louise; Desmeules, Martin (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
Chapter: 5

Francophone seniors in Ontario: A health portrait - Bouchard, Louise; Makvandi, E.; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, University of Ottawa, 2014)

Les aînés francophones de l’Ontario : un portrait de santé. - Bouchard, Louise; Makvandi, Ewa; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, Université d'Ottawa, 2014)

The health of the Francophone population aged 65 and over in Ontario. A region-by-region portrait based on the Canadian community health survey (CCHS) - Bouchard, Louise; Makvandi, Ewa; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario & University of Ottawa, 2014)

Comment améliorer la santé des aînés francophones vieillissant en Ontario ? Entre approche populationnelle et santé communautaire - Bouchard, Louise; van Kemenade, Solange (La santé communautaire en 4 actes : repères, acteurs, démarches et défis, 2016)
fs-ref-orig: Bouchard, L. et van Kemenade, S. (2016). Comment améliorer la santé des aînés francophones vieillissant en Ontario ? Entre approche populationnelle et santé communautaire. Dans V. Desgroseillers, N. Vonarx, A. Guichard et B. Roy (dir.), La santé communautaire en 4 actes : repères, acteurs, démarches et défis (p. 132-137). Presses de l’Université Laval. fs-code-orig: Bouchard-2016

La santé des aînés francophones en situation linguistique minoritaire : états des lieux en Ontario - Bourbonnais, Valérie (Université d’Ottawa, 2007)
L'objectif de cette thèse est de tracer les profils comparatifs des états de santé des populations francophones et anglophones âgées de 65 ans et plus de l'Ontario en utilisant les données de l'Enquête sur la santé et les collectivités canadiennes (ESCC) recensées par Statistique Canada. Dans un deuxième temps, ces profils seront également analysés en fonction du genre. Or, trois grands volets seront examinés dans ce projet: (1) les caractéristiques socio-démographiques, (2) les états de santé déclarés et perçus, (3) ainsi que l'utilisation et la satisfaction à l'égard des services de soins de santé. L'objectif principal de cette thèse est de démontrer que le fait de vivre dans un contexte linguistique minoritaire engendre des facteurs risquant d'influencer négativement le vieillissement de la minorité sociolinguistique francophone de l'Ontario. En puisant à la discipline sociologique, une théorisation de la minorité sera utilisée afin d'appuyer la thèse avancée. Globalement les analyses révèlent un profil socioéconomique et un profil de santé plus précaires chez les aînés de la minorité francophone comparativement aux aînés de la majorité anglophone. Il est intéressant de noter que cette précarité de la santé s'exprime autant chez les hommes que chez les femmes de la minorité francophone, malgré que celle-ci s'articule différemment pour certaines variables. Quant à la prestation des services de soins de santé, les aînés de la minorité francophone sont unanimement insatisfaits de l'accessibilité, ainsi que de la qualité des services dans l'ensemble de la province ontarienne.

Les francophones de l'Ontario de 65 ans et plus : un profil statistique - Cardinal, Linda; Plante, Nathalie; Sauvé, Anik (Chaire de recherche sur la francophonie et les politiques publiques et Université d'Ottawa, 2006)
fs-ref-orig: Cardinal, L., Plante, N. et Sauvé, A. (2006). Les francophones de l'Ontario de 65 ans et plus : un profil statistique. Chaire de recherche sur la francophonie et les politiques publiques et Université d'Ottawa. fs-code-orig: Cardinal-2006

Initiatives intergénérationnelles en santé. Rapport final - Duguay, Benoît (La Commission nationale des parents francophones, la Fédération des aînées et aînés francophones du Canada et la Société Santé en français, 2007)
fs-ref-orig: Duguay, B. (2007). Initiatives intergénérationnelles en santé. Rapport final. La Commission nationale des parents francophones, la Fédération des aînées et aînés francophones du Canada et la Société Santé en français. fs-code-orig: Duguay-2007a

La prise en compte de la langue dans les foyers de soins pour personnes âgées - Forgues, Éric; Gaucher, Charles; Guignard Noël, Josée; Kabano, John; Michaud, Jacques (Institut canadien de recherche sur les minorités linguistiques, 2012)

Vieillir en situation linguistique minoritaire au Canada et ses implications pour la santé [infographie] - Gagnon-Arpin, Isabelle; Bouchard, Louise; Gaboury, Isabelle; Bourbonnais, V.; Chomienne, Marie-Hélène (2009)
fs-ref-orig: Gagnon-Arpin, I., Bouchard, L., Gaboury, I., Bourbonnais, V. et Chomienne, M.-H. (2009). Vieillir en situation linguistique minoritaire au Canada et ses implications pour la santé [infographie]. Réseau de recherche interdisciplinaire sur la santé des francophones en contexte minoritaire au Canada (RISF), Université d’Ottawa. fs-code-orig: Gagnon-Arpin-2009a

Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report - Summary. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français. Rapport de recherche - Résumé. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)

Maintien à domicile francophone - Martel, Richard; Pinsonneault, Carole (Reflets, 1996)

L'état de santé des personnes âgées francophones en Ontario - McKellar, Jocelyne (Reflets, 1999)

La prise en compte du français dans l’organisation des services en foyers de soins majoritairement anglophones au Canada - Michaud, Jacques; Forgues, Éric; Guignard Noël, Josée (Minorités linguistiques et société, 2015)
L’accès aux services de santé en français préoccupe grandement les communautés francophones vivant en situation minoritaire. Le présent article offre un survol de l’espace francophone dans les résidences collectives d’aînés du Nouveau-Brunswick, de la Nouvelle-Écosse et de l’Ontario à la lumière d’une recherche exploratoire menée en 2012. L’analyse des données obtenues auprès d’aînés, d’aidants et du personnel, l’examen de la répartition géographique des résidences et de la population d’aînés francophones, ainsi qu’un aperçu du contexte réglementaire encadrant le fonctionnement de ces résidences permettent de définir la problématique pertinente. Des actions en vue d’améliorer la situation sont examinées. Mots-clés : espace francophone, services de santé en français, francophones en situation minoritaire, foyers de soins, résidences collectives, vieillissement de la population

Vers des services attirants, accessibles et pertinents pour les personnes âgées immigrantes francophones ? - Nduwimana, Mathilde; Home, A. (Reflets, 1995)
Cet article décrit et analyse les besoins et préoccupations des personnes âgées autonomes appartenant aux groupes ethniques francophones et résidant dans Ottawa-Carleton. L'objectif principal est d'explorer les raisons pour lesquelles elles utilisent peu les services de soutien communautaires pour les personnes âgées francophones. Nous avons effectué des entrevues semi-structurées auprès de quatre représentantes et de six personnes âgées des communautés ethno-culturelles francophones, et nous avons effectué une analyse de contenu par thème. Les répondantes ont souligné les besoins de contacts sociaux, d'apprentissage du français et/ou de l'anglais, d'accès aux moyens financiers adéquats et d'information sur les ressources disponibles. Des obstacles liés au contexte socio-écono-politique dans la société d'accueil entravent la satisfaction de ces besoins. La levée de certaines barrières concrètes, la modification des politiques sociales et des pratiques d'intervention faciliteraient l'accès aux services par les personnes âgées des groupes ethniques francophones et augmenteraient leurs options.

Cognitive health initiative for Francophone seniors in the GTA - Reflet Salvéo; Entité 4 (Options fo Service Models, 2017)
fs-ref-orig: Reflet Salvéo, & Entité 4. (2017). Cognitive health initiative for Francophone seniors in the GTA. Options fo Service Models. fs-code-orig: Reflet Salvéo-2017

Rapport sur l’accès aux soins de longue durée en français dans la région de Champlain. Sommaire - Réseau des services de santé en français de l’Est de l’Ontario (2020)
fs-ref-orig: Réseau des services de santé en français de l’Est de l’Ontario. (2020). Rapport sur l’accès aux soins de longue durée en français dans la région de Champlain. Sommaire. fs-code-orig: Réseau des services de santé en français de l’Est de l’Ontario-2020

Guide de planification et de prestation des soins de longue durée en français. Leçons tirées du pavillon Omer Deslauriers de Bendale Acres et d'autres services de santé en français pour aînés au Canada - Réseau franco-santé du Sud de l’Ontario (2017)

Strategies to improve French language health and social service continuity for seniors in Ontario and Manitoba - Savard, Jacinthe; Savard, Sébastien; de Moissac, Danielle; Giasson, Florette; Kubina, Lucy-Ann (Linguistic Minorities and Society, 2021)
Access to health and social services in one’s official language of choice is an important component of quality and safety of care for seniors. Access can be fragmented, even in the context of legislation guaranteeing the right to receive such services, and in areas with a higher proportion of bilingual providers. Using a community-based participatory approach, we identified mechanisms promoting or impeding the clinical integration of health and social French language services intended for seniors living in two Canadian Francophone minority communities. Thirteen recommendations highlight the possibility for new initiatives to promote a continuum of French language health and social services in a minority context, involving collaboration among a variety of actors at all levels of our analytical framework: service trajectory (providers); francophone communities; organizational; political and regulatory; and symbolic (values) structures. Keywords: seniors, linguistic minorities, service integration, health and social services, continuity of care

Le vieillissement francophone en contexte minoritaire. Défis et opportunités - Siméon, Frantz; Couturier, Yves (Reflets, 2021)

Differences between the francophone and Anglophone ethno-linguistic groups in the Ontario home care setting [master's thesis, Lakehead University] - Thériault, Eric. R. (2009)
fs-ref-orig: Thériault, E. R. (2009). Differences between the francophone and Anglophone ethno-linguistic groups in the Ontario home care setting [master's thesis, Lakehead University]. Lakehead University Library. http://knowledgecommons.lakeheadu.ca/handle/2453/204 fs-code-orig: Thériault-2009